An Experimental Murine Model to Study Periodontitis - Marchesan, Julie (Nat Protoc, 2018)
Periodontal disease (PD) is a common dental disease associated with the interaction between a dysbiotic oral microbiota and host immunity. It is a prevalent disease resulting in loss of gingival tissue, periodontal ligament, cementum, and alveolar bone. PD is a major form of tooth loss in the adult population. Experimental animal models have enabled the study of PD pathogenesis and are used to test new therapeutic approaches for treating disease. The ligature-induced periodontitis model has several advantages compared to other models, including rapid disease induction, predictable bone loss, and the capacity to study periodontal tissue and alveolar bone regeneration due to the model being established within the periodontal apparatus. Although mice are the most convenient and versatile animal models used in research, ligature-induced periodontitis has been more frequently used in large animals. This is mostly due to the technical challenges required to consistently place ligatures around murine teeth. To reduce the technical challenge associated with the traditional ligature model, we previously developed a simplified method to easily install the bacterial retentive ligature between 2 molars for inducing periodontitis. In this protocol we provide detailed instructions for placement of the ligature and demonstrate how the model can be used to evaluate gingival tissue inflammation and alveolar bone loss over an 18 day period following ligature placement. This model can also be used on germ free mice to investigate the role of human oral bacteria in periodontitis in vivo. In conclusion, this protocol enables the mechanistic study of the pathogenesis of periodontitis in vivo.